Black silicon back‐contact module with wide light acceptance angle. (11th December 2019) - Ortega, Pablo; Garín, Moises; von Gastrow, Guillaume; Savisalo, Tuukka; Tolvanen, Antti; Vahlman, Henri; Vähänissi, Ville; Pasanen, Toni P.; Carrió, David; Savin, Hele; Alcubilla, Ramón
Abstract: In this work, a photovoltaic mini‐module combining interdigitated back‐contacted solar cells with black silicon in the front was implemented as a proof of concept. The module consists of nine solar cells connected in series with an active area of 86.5 cm 2 . Both the assembly and panel encapsulation were made using industrial back‐contact module technology. Noticeable photovoltaic efficiencies of 18.1% and 19.9% of the whole module and the best individual cell of the module, respectively, demonstrate that fragile nanostructures can withstand standard module fabrication stages. Open‐circuit voltage and fill factor values of 5.76 V and 81.6%, respectively, reveal that series interconnection between cells works as expected, confirming a good ohmic contact between cell busbars and the conductive backsheet. Additionally, the excellent quasi‐omnidirectional antireflection properties of black silicon surfaces prevail at module level, as it is corroborated by light incidence angle dependence measurements of the short‐circuit current parameter. Abstract : A photovoltaic mini‐module combining interdigitated back‐contacted solar cells with black silicon in the front was implemented. The module consists of nine solar cells connected in series with an active area of 86.5 cm 2 . Both the assembly and panel encapsulation were made using convectional industrial back‐contact module technology. A noticeable photovoltaic module efficiency of 18.1% demonstrates that fragile nanostructures can withstand standard module fabrication stages.